Global, regional and national estimates of influenza-attributable ischemic heart disease mortality. (January 2023) - Chaves, Sandra S.; Nealon, Joshua; Burkart, Katrin G.; Modin, Daniel; Biering-Sørensen, Tor; Ortiz, Justin R.; Vilchis-Tella, Victor M.; Wallace, Lindsey E.; Roth, Gregory; Mahe, Cedric; Brauer, Michael
Summary: Background: Influenza virus infection is associated with incident ischemic heart disease (IHD) events. Here, we estimate the global, regional, and national IHD mortality burden attributable to influenza. Methods: We used vital registration data from deaths in adults ≥50 years (13.2 million IHD deaths as underlying cause) to assess the relationship between influenza activity and IHD mortality in a non-linear meta-regression framework from 2010 to 2019. This derived relationship was then used to estimate the global influenza attributable IHD mortality. We estimated the population attributable fraction (PAF) of influenza for IHD deaths based on the relative risk associated with a given level of weekly influenza test positivity rate and multiplied PAFs by IHD mortality from the Global Burden of Disease study. Findings: Influenza activity was associated with increased risk of IHD mortality across all countries analyzed. The mean PAF of influenza for IHD mortality was 3.9% (95% uncertainty interval [UI] 2.5–5.3%), ranging from <1% to 10%, depending on country and year. Globally, 299, 858 IHD deaths (95% UI 191, 216–406, 809) in adults ≥50 years could be attributed to influenza, with the highest rates per 100, 000 population in the Central Europe, Eastern Europe and Central Asia Region (32.3; 95% UI 20.6–43.8), and in the North Africa and Middle East Region (26.7; 95% UI 17–36.2). Interpretation: Influenza may contribute substantially to the burden of IHD. Our results suggest that if there were no influenza, an average of 4% of IHD deaths globally would not occur. Funding: Collaborative study funded by Sanofi Vaccines.